Social Behavior and Local Plants in the Nolloth and Tuhaha Villages, East Saparua District, Central Maluku Regency - Frans, Jouverd Fendli; Titaley, Elsina; Manuputty, Pieter H.; Alfons, Christwyn R. (Unram Journal of Community Service, 2025)
Natural resources found on land in local plantations in Maluku, especially among indigenous communities in their petuanan (land holdings), constitute both individual and community wealth. Ownership of plantation land with economic value can support community well-being, particularly the production of local crops, which have been a favorite from ancient times to the present day. Cloves, while always possessing economic value, also possess historical and cultural values ​​deeply embedded in the community. Ancestors, in their time, established a local plant ecosystem with strategic long-term economic value for themselves, their children, and grandchildren. The purpose of these plants was to enable parents to provide economic protection for their families. Thus, with the presence of local clove plants, a long-lived plant, economic security and prosperity are ensured for their descendants. Being lulled by the legacy of plants passed down from parents or ancestors has resulted in the current rejuvenation process being devalued, as social shifts in perspectives have rendered today's descendants oblivious to the existence of these local plants. It is important to build awareness and social behavior in the community regarding the importance of local plants as a long-term economic strategy, but also as a socio-cultural identity of the local community